Reflectivity of Bragg grating fiber on human respiration using InGaAs photodiode converter system - Oktavia, Dian Putri; Saktioto, Saktioto; Hanto, Dwi; Syamsudhuha, Syamsudhuha; Amelia, Rina; Emrinaldi, Tengku (Indonesian Physics Communication, 2025)
Respiration is a vital process characterized by exchanging oxygen and carbon dioxide. Indicators such as respiratory rate are essential for detecting pathological conditions, such as pneumonia and heart failure. This research aims to develop a respiratory sensor system based on fiber Bragg grating (FBG) as an innovative alternative in high electromagnetic field environments. The system utilizes FBG optical fibers to detect strain changes due to respiratory activity, providing a sensitive, safe, and highly electromagnetic environment-compatible solution. The study used FBG with variations in reflectivity of 30%, 50%, 70%, and 90%. FBGs are installed inside oxygen masks at five different points to monitor wavelength changes during respiratory activity. The measurement method involves an optical system with an interrogator and an electrical method using an InGaAs photodiode converter to convert an optical signal into an electrical signal visualized in LabVIEW. Respondents were tested in three activities: stillness, walking, and running. Variations in sensor reflectivity and position in masks were evaluated to determine sensitivity to respiratory changes. The data is collected as a graph of wavelength against time. The result showed that the change in the wavelength of the FBG correlated with the intensity of respiratory activity. The reflectivity of 90% results in the highest sensitivity, allowing for more accurate detection of strain changes. The position of the sensor at the center point of the mask demonstrates the most linear results, indicating optimal sensitivity. Physical activity, such as running, produces the greatest strain on the optical fiber. This study proves the potential of FBG as a precision medical sensor for respiratory monitoring applications.